Electro-mechanical sensing in freestanding monolayered gold nanoparticle membranes. Issue 22 (19th May 2016) - Gauvin, M.; Grisolia, J.; Alnasser, T.; Viallet, B.; Xie, S.; Brugger, J.; Ressier, L.
Abstract : The electro-mechanical coupling in freestanding monolayered membranes of self-assembled gold nanoparticles shows high strain sensitivity owing to the exponential dependence of the tunnel electron transport in 2D nanoparticle arrays on the strain-induced length variation of the interparticle junctions. Abstract : The electro-mechanical sensing properties of freestanding monolayered membranes of dodecanethiol coated 7 nm gold nanoparticles (NPs) are investigated using AFM force spectroscopy and conductive AFM simultaneously. The electrical resistance of the NP membranes increases sensitively with the point-load force applied in the center of the membranes using an AFM tip. Numerical simulations of electronic conduction in a hexagonally close-packed two-dimensional (2D) array of NPs under point load-deformation are carried out on the basis of electronic transport measurements at low temperatures and strain modeling of the NP membranes by finite element analysis. These simulations, supporting AFM-based electro-mechanical measurements, attribute the high strain sensitivity of the monolayered NP membranes to the exponential dependence of the tunnel electron transport in 2D NP arrays on the strain-induced length variation of the interparticle junctions. This work thus evidences a new class of highly sensitive nano-electro-mechanical systems based on freestanding monolayered gold NP membranes.